2009
DOI: 10.32894/kujss.2009.40784
|View full text |Cite
|
Sign up to set email alerts
|

Geochemical Evaluation of Heavy Metals Pollution of Industrial Quarter Soils at Kirkuk City .Northern Iraq

Abstract: The study is concerned with geochemical evaluation of heavy metals pollution in Kirkuk soil,northern Iraq.Samples were collected from twenty-eight locations of surface soils at Kirkuk industrial quarter.The results obtained from heavy metals determination in this study showed that the concentration of Pb ranged from 71 to 433 mg/kg,Ni concentration was from 49 to 285mg/kg,Zn ranged from 32to 186 mg/kg,Cd,Cr and Cu were in the range from 1.0 to 4.9 mg/kg,15 to 198 mg/kg and 24 to 182 mg/kg respectively.Variance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Also the reason may be that the province of Kirkuk suffers pollution but in different degrees and from different sources due to the existence of different factories and petrochemical plants (cement, North Oil Company and North Gas Company), pollutants emitted from them, vehicle exhausts and residues directly from residential in addition to chemical fertilizers and various pesticides added (89.8, 13.9, 12.1, 335.2 ppm) and were higher than the average (18). Also (4) show the concentration of cadmium, lead and zinc is high reached (3.55, 433, 186 ppm) in soil of Kirkuk. The increase in the level of pollution in the soil of Kirkuk effects on the level of concentration of the element in animal meat through its impact on the soil, plants and environment of the location, it was noted in the soil of Kirkuk high level of contamination with the copper (42 ppm) (15).The reason is that there are large numbers of people, large and small markets, streets, shops selling animal products The absence of a sewage system, the absence of a building plan, and the large number of oil and gas fields all have polluted the Kirkuk environment (11).…”
Section: Yijklm = M + Ai + Bj + Ck + Cd (Kl) + Abc (Ijk) + E Ijklmmentioning
confidence: 85%
See 1 more Smart Citation
“…Also the reason may be that the province of Kirkuk suffers pollution but in different degrees and from different sources due to the existence of different factories and petrochemical plants (cement, North Oil Company and North Gas Company), pollutants emitted from them, vehicle exhausts and residues directly from residential in addition to chemical fertilizers and various pesticides added (89.8, 13.9, 12.1, 335.2 ppm) and were higher than the average (18). Also (4) show the concentration of cadmium, lead and zinc is high reached (3.55, 433, 186 ppm) in soil of Kirkuk. The increase in the level of pollution in the soil of Kirkuk effects on the level of concentration of the element in animal meat through its impact on the soil, plants and environment of the location, it was noted in the soil of Kirkuk high level of contamination with the copper (42 ppm) (15).The reason is that there are large numbers of people, large and small markets, streets, shops selling animal products The absence of a sewage system, the absence of a building plan, and the large number of oil and gas fields all have polluted the Kirkuk environment (11).…”
Section: Yijklm = M + Ai + Bj + Ck + Cd (Kl) + Abc (Ijk) + E Ijklmmentioning
confidence: 85%
“…Table (4) showed the effect of the location on the level of contamination of the copper element. It was found that there were significant effects (P≤0.05) between the Downtown and the both Dubs and Daquq and no significant effects (P> 0.05) between both Daquq and Dubs in all types of meat (muscle, liver and kidney), The concentration of copper in the Downtown reached the highest level (13.451 ppm) and the lowest level of concentration was recorded in Dubs (5.231 ppm) in the liver.…”
Section: Yijklm = M + Ai + Bj + Ck + Cd (Kl) + Abc (Ijk) + E Ijklmmentioning
confidence: 99%
“…Also, relatively high concentrations appeared at sites H5 and H7, as their concentration (50 mg/kg) was both, the H5 site represents Shoraw neighborhood which passes through the highway link Kirkuk and Erbil and is characterized by heavy traffic, which may contribute to increasing the concentration of vanadium, also its location is near the oil company and the Kirkuk refinery and on the northeast side in the same direction as the prevailing wind in the city which contribute of transfer vanadium-rich emissions and deposited in it (Al-Hamdani et al, 2016;AL-Jumaily, 2009 andAwadh andAl-hamdani, 2019). As for the site H7 it represents farm in Mamdoda area and its increase in the concentration of vanadium is due to the use of phosphate fertilizers as mentioned above.…”
Section: Vanadium Content In the Soil Of The Study Areamentioning
confidence: 99%